Pride and Prejudice: Pervasiveness of Colorism and the Animated Series Proud Family. Issue 1 (2nd January 2016) - Steele, Catherine Knight
ABSTRACT: Issues of race and racism continue to be subjects of interest for media critique; however, the more subtle notion of colorism is often ignored in the examination of media texts. An analysis of the popular children's animated series Proud Family demonstrates that even in a context where a "traditional" African American family and positive community relations are shown, colorism is still prominent. Rather than being critiqued or challenged, kids' media is used to reinforce colorist ideals within the African American community. Attributes of wealth, beauty, and intelligence are applied to characters with Eurocentric phenotypic characteristics while deviance, stupidity, poverty and unattractiveness typify characters with more Afrocentric facial features.